A Cross‐Cultural Examination of the Disjuncture Between Aspirations and Expectations/Perceived Outcomes: Strain and Academic Deviance in the United States and Japan1. Issue 3 (23rd May 2015) - Tedor, Miyuki Fukushima; Sharp, Susan F.; Kobayashi, Emiko
<x xml:space="preserve">Abstract</x> Using comparable self‐reported survey data collected among college students in the United States (n = 502) and Japan (n = 441), this study examines a paradox of higher academic deviance among otherwise more conforming Japanese youth while revisiting the debate concerning the disjuncture between aspirations and expectations/perceived outcomes in Agnew's general strain theory (GST). Confirming the paradox, our results indicate that Japanese students are significantly more deviant academically than American students. However, contrary to the expectation of GST, but in support of past empirical studies, the higher academic deviance among the Japanese, as compared to Americans, is explained by their lower aspirations, irrespective of the levels of expectations/perceived outcomes